Effects of dietary chromium picolinate and ascorbic acid supplementation on egg production, egg quality and some serum metabolites of laying hens reared under a low ambient temperature (6°C) - Şahin, Kazım; Onderci, M; Şahin, Nurhan; Aydin, S (Taylor & Francis Ltd, 2002)
This experiment was conducted to evaluate the effects of chromium (chromium picolinate, Cr Pic) and vitamin C (L-ascorbic acid) supplementation on egg production and egg quality in laying hens (Hy-Line) kept at 18degreesC (at thermo-neutral zone) or 6degreesC (cold stress) in temperature-controlled rooms. One hundred and fifty laying hens (32 week-old) were divided into 5 groups, 30 hens per group. The laying hens kept at 6degreesC temperature were fed either a basal diet (low temperature-basal diet, LTB group) or the basal diet supplemented with either 400 mug of Cr per kg diet (Cr group), 250 mg of L-ascorbic acid per kg diet (Vit C group) or 400 mug of Cr plus 250 mg of L-ascorbic acid per kg diet (Vit C + Cr group) while hens kept at 18degreesC fed a basal diet (thermo-neutral-basal diet, TNB group). Performance and egg quality were significantly reduced in LTB group compared with TNB group. Supplemental chromium and vitamin C significantly increased live weight change, egg production, and improved feed efficiency in cold-stressed hens compared with group fed the basal diet at 6degreesC brought up to the values of the group reared under thermoneutral conditions (18degreesC). Egg production and egg weight were also greater in each supplemental group compared with the LTB group. Separately or as a combination, supplemental chromium and vitamin C increased serum insulin but decreased corticosterone, glucose and cholesterol concentrations. Results of the present study show that supplementing vitamin C and chromium, particularly as a combination, improved the performance of cold-stressed hens. Such a combination of supplement can offer a potential protective management practice in preventing cold stress-related losses in performance of laying hens.
Keywords: cold stress; chromium; vitamin C; egg; laying hen